SAT0660 Safety, feasibility and tolerability of performing consecutive minimal invasive ultrasound-guided synovial biopsy procedures on the same wrist in a prospective rheumatoid arthritis study. (15th June 2017) - Just, SA; Nielsen, C; Hejbøl, EK; Schrøder, HD; Hansen, IMJ; Barington, T; Lindegaard, HM
Abstract : Background: Studies on synovial tissue retrieved using the minimal invasive ultrasound-guided synovial biopsy (USG-SB) method have led to major advances in the understanding of Rheumatoid Arthritis (RA). The method is now used in multicenter RA studies and recommended in the phases of RA drug development. Only to biopsy disease active joints at start and end of a study, can lead to biopsies being retrieved from different joints. This can make interpretation of the changes in the synovial tissue and gene-expression profile difficult, as synovial histology patterns can vary between joints. We here present an approach where we biopsied the wrist with disease activity at presentation and the same wrist after six month of disease duration. We use the wrist, as it is the joint most commonly involved in the upper extremity in RA. The joint is easily accessible for USG-SB and therefore ideal to use to follow disease activity/treatment response/biomarker change in prospective RA studies. Objectives: To assess the safety, tolerability and feasibility to perform repeated synovial biopsies from the same wrist, using a minimally invasive USG-SB technique in patients suffering from RA. Methods: Patients with newly diagnosed untreated RA or longstanding (>5 years) RA and at least one clinically swollen wrist, underwent x-ray, magnetic resonance imaging (MRI) and ultrasound examination of the affected wrist and hand on the day of the biopsy. This was repeated 6 months later, where the second biopsy from the same wrist was taken. EULAR guidelines for RA treatment were followed in the 6 months between biopsies. Patient-reported outcomes (PRO) included a standard questionnaire given to all patients on the day of the biopsy as well as 2 weeks after the biopsy. Tolerability and the patient-reported willingness to repeat the procedure was assessed using the 5-point Likert scale. Results: 38 RA patients (22 early, 16 longstanding) underwent USG-SB procedure at inclusion and after 6 months. One patient was excluded and did not have second biopsy due to diagnosis of CPPD. All patients have undergone first biopsy and at present time and 50% second biopsy. At the EULAR congress complete data will be presented. At present time, at both first and second biopsy no worsening in PRO of the biopsied joints was reported 2w after the biopsy, as compared before the biopsy. No infection, hemorrhage, nerve or tendon damage has currently been observed. One patient developed a tenosynovitis after biopsy (the CPPD patient), successfully treated with glucocorticoid injection. 10% of the patients were somewhat or very unlikely to have another biopsy procedure after the first procedure, and 6% after the second. All included RA patients accepted to have a second biopsy. Detailed data on differences in tolerability between early untreated RA patients versus patients with longstanding RA, will be presented at the conference. Conclusions: To our knowledge, we are the first, to demonstrate that retrieving synovial tissue using the USG-SB method on the same wrist, at start and end of a prospective RA study, is safe and well tolerated. Disclosure of Interest: None declared